Nuevas alfabetizaciones en un entorno multimodal: nuevas necesidades lectoras para un entorno textual múltiple - Juan Patricio Sánchez Claros (Investigaciones Sobre Lectura)
The new technologies of information, the development of the media and the massive presence of multimedia devices have brought a renewal of the traditional concept of literacy. Multimodality in the media, in the dissemination of knowledge and the communication formats have brought a change in the system of reception of media objects and each of its integral elements. This multimodal environment is part of the daily life of students who access through a scenario of screens and images across a virtual environment in which both textual and visual are integrated as an informational continuum that requires to users new interpretation skills. And, consequently, a new approach to media literacy should be the subject of attention from educators. Media literacy implies the need to address new visual skills, new reading skills and especially new skills for integration and analysis, among those who cannot be set aside on the critical apparatus necessary. This paper discusses the content of these skills, some critical tools for multimodal approach speech as well as the role the four substrata of discourse, design, production and distribution, typical of Critical Analysis of Multimodal Discourse are analysed.